River-sourced Cladophora glomerata macroalgal biomass as a more sustainable and functional feed raw material for growing rabbits - Monika Nutautaitė; Asta Racevičiūtė-Stupelienė; Saulius Bliznikas; Alius Pockevičius; Vilma Vilienė (Italian Journal of Animal Science)
Animal scientists actively seek strategies for ensuring the sustainable viability of animal ecosystems, with a focus on exploring alternative feed raw materials to reduce reliance on traditional ones. So, this study aims to analyse the impact of river-sourced Cladophora glomerata macroalgal biomass on the growth, slaughter performance, and physiological development of rabbits. Thirty weaned (52 days of age) Californian rabbits were assigned to three dietary treatments: standard compound diet (SCD), SCD enriched with 4% C. glomerata (CG4), and SCD enriched with 8% C. glomerata (CG8). Growth performance was recorded throughout the feeding trial, and at its conclusion (122 days of age), rabbits were euthanized, slaughtered, and subjected to intestinal analysis. Incorporation of CG diets showed no significant impact on body weight or average daily gain (p > 0.05); however, CG8 significantly lowered daily feed intake and feed conversion ratio (p < 0.05). The SCD resulted in a significantly higher lung percentage (p < 0.05), while CG diets had minimal effects on remaining slaughter performance traits. In duodenal content, CG-enriched diets increased acetic and propionic acid levels but reduced lactic (p < 0.05). Duodenal villus height remained stable, while in the ileum, CG4 inclusion resulted in a significantly higher villus (p < 0.05). Duodenal crypt depth increased with biomass supplementation; conversely, in the ileum, increased biomass led to decreased crypt depth (p < 0.05). In general, recent research suggests that adding C. glomerata to rabbit diets can be an effective alternative without adverse effects on growth, slaughter performance, or physiologial development.